2022
DOI: 10.1038/s41559-022-01846-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical dose responses shape the evolutionary trade-off between antifungal resistance and nutrient use

Abstract: Antimicrobial resistance is an emerging threat for public health. The success of resistance mutations depends on the trade-off between the benefits and costs they incur. This trade-off is largely unknown and uncharacterized for antifungals. Here, we systematically catalog the effect of all amino acid substitutions in the yeast cytosine deaminase FCY1, the target of the antifungal 5-FC. We identify over 900 missense mutations granting resistance to 5-FC, a large fraction of which appear to act through destabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 91 publications
2
28
1
Order By: Relevance
“…For instance, many combinations of transcription and translation rates can lead to the same amount of protein ( 33 ). Coding mutations that increase protein abundance, for instance, through codon usage ( 23 ), can therefore be beneficial at low promoter activity, as we observed here. Even if they produce similar steady-state amounts of proteins, combination of transcription and translation rates and protein stability are not evolutionarily equivalent because of selection on other features such as expression noise ( 33 ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…For instance, many combinations of transcription and translation rates can lead to the same amount of protein ( 33 ). Coding mutations that increase protein abundance, for instance, through codon usage ( 23 ), can therefore be beneficial at low promoter activity, as we observed here. Even if they produce similar steady-state amounts of proteins, combination of transcription and translation rates and protein stability are not evolutionarily equivalent because of selection on other features such as expression noise ( 33 ).…”
Section: Discussionsupporting
confidence: 58%
“…We next examined whether the higher observed activity of the E2R and E2V mutants could be caused by higher protein abundance. Nucleotide content and their corresponding amino acids in the first few codons of a gene are known to modulate protein expression in E. coli ( 23 ), which makes this region a target for beneficial mutations when transcription levels are low. To test the effect of amino acid changes on protein abundance, we generated GFP fusions with (i) the entire DfrB1 WT sequence with and without (ii) the most beneficial mutation (E2R), (iii) the WT disordered N-terminal region (amino acids 1 to 25), and (iv) the disordered region with the E2R mutation (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when we compared the relative fitness measured in liquid medium versus the one measured on solid medium, we observed that the fcy1 Δ mutant shows a significant fitness defect on solid medium when grown alongside other mutants (Supp Fig 7B). A recent study by our group showed that fcy1 Δ could grow on plates supplemented with cytosine as the only nitrogen source as long as strains with a functional FCY1 allele ( FCY1 + ) were growing in proximity [41]. The auxotrophy of a fcy1 Δ strain can therefore be rescued by cross-feeding uracil from FCY1 + strains.…”
Section: Resultsmentioning
confidence: 99%
“…We assess this by introducing all possible single amino acid substitutions in the two paralogous SH3 domains using saturation mutagenesis and CRISPR-Cas9-based homology repair (Fig 1B). We inserted complete single amino acid mutant libraries directly into the yeast genome 29, 45, 46 and quantified the functional impact of these mutations on their ability to interact with eight representative cognate partners in the protein interaction network regulating yeast endocytosis (Fig 1C). To assess the impact of regulatory divergence between the two genes 47 and changes in sequence context in the rest of the protein 29, 48, 49 , we measured the same effects of all mutations by swapping the domains between the paralogous myosins (Fig 1B), that is, expressing a Myo5 protein carrying the Myo3 SH3 domain and vice versa.…”
Section: Introductionmentioning
confidence: 99%